Ter herinnering aan de eerste steenlegging van het "Arbeidershuis" en "Kantoorgebouw" van de Centrale - Welij, V. (1906)
Ter herinnering aan de eerste steenlegging van het "Arbeidershuis" en "Kantoorgebouw" van de Centrale.